Research on extracting mental lexicon from legal cases of players based on text features - Yan Fan; Helen wake; Julius Taba; Elizabeth cooper (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Mental lexicon extraction has important theoretical and practical significance in legal case judgment; however, mental lexicon cannot be extracted in time and effectively. Therefore, this paper puts forward the research on the extraction method of mental lexicon in legal cases of players based on text features. In terms of extraction factors of mental lexicon in legal cases of players, quantity and quality are the two most important factors, and form an important reference for mental lexicon recognition. Therefore, it should be combined with text features to identify and extract mental lexicon frequency, and the extraction process is described in detail in this paper by using pattern recognition theory. The psychological test is applied to test the biological reaction of the suspect to determine and judge the relationship between the suspect and the case to ensure the accuracy of the case.